The Benefit of Utilizing E-Government Based Public Services - Muhammad Iqbal; Julia Ivanna; Sri Hadiningrum (Randwick International of Social Science Journal, 2020)
The aim of this article to research government efforts in the implementation of bureaucracy reform as stipulated in the law No. 25 of 2009 about public services related to the service to its residents with quality service standards, fast, easy, affordable and be measured. It is in accordance with Presidential Instruction No. 3 of 2003 about national policy on e- Government development. In its development, e-Government is still far from expectations, government institutions both in the center and the region do not yet consider the important e-Government. E-Government is considered a project and a one of the sub-districts in Medan that has been conducting bureaucracy reform by providing public services based on electronic (e-kecamatan) in managing Administration and Increase Community participation. This study uses qualitative research methods with the type of descriptive research. The results showed the success of public services electronic-based public services in Kecamatan Medan Barat had a prerequisite, namely (1) the support from the District Leadership (Camat), (2) availability of Financial Resources and Human Resources (3) Transparency In the public service process with application system. In addition, e-kecamatan based momentarily trend. Kecamatan Medan barat where the research will be done services facilitate the residents to obtain information and manage various purposes in the form of administrative services products.